Review of the Early Bronze Age Book of Tepeköy Höyük Excavations in the Varto District of Muş Province - ÇİFÇİ, ALİ (My University, 2024)
The book, prepared with the contributions of Energo-Pro, consists of three presentations and 11 chapters; each chapter contains an English abstract. The book includes the results of rescue excavations carried out in 2014, 2017, and 2018 at Tepeköy Höyük in the Varto district of Muş province under the direction of the Ahlat Museum within the scope of the Alpaslan II Dam and Hydroelectric Power Plant project. Increasing population and energy needs with urbanisation necessitate the development of dams and similar projects. However, dam or Hydroelectric Power Plant projects have become the biggest cause of the disappearance or destruction of cultural heritage, especially ancient settlements in the areas where they are built (Özdoğan 2008). In the planning processes of dams or similar projects, it is important to identify the cultural and natural monuments that will remain within the impact areas and to develop these projects accordingly or to revise them at the project stage to protect or minimise the impacts of such projects on cultural heritage. Cultural heritage sites in the vicinity of dam projects should be systematically surveyed prior to construction, or if they have to be relocated, necessary measures should be taken to prevent their destruction and protection measures should be developed.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Eskiçağ Tarihi; Anadolu Medeniyetleri Ve Kültür Mirası Yönetimi; Arkeoloji ve Sanat Tarihi; Social Sciences and Humanities; History; Ancient History; Heritage Management for Anatolian Civilizations and Culture; Archaelogy and History of Art; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; ARKEOLOJİ; TARİH; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; ARCHAEOLOGY; HISTORY; Arkeoloji; Arkeoloji (sanat ve beşeri bilimler); Sosyal Bilimler ve Beşeri Bilimler; Archeology; Archeology (arts and humanities); Social Sciences & Humanities; Early Bronze Age; Eastern Anatolia; Tepeköy Höyük; Cultural Heritage; Rescue Excavations